Theoretical aspects of sorption refrigeration using organic compounds - Jin, Meihua (Department of Mechanical Engineering, 2016)
Refrigeration devices for essential food storage and preservation of medicine are among the most significant techniques developed in the past few decades. In many regions of Africa, the shortage of sustainable power sources and the abundance of solar energy make solar refrigerators a promising solution for basic refrigeration needs. Among all the solar cooling techniques, the solar sorption refrigerator is considered to be a promising alternative to the dominant vapour-compression refrigerator, which encompasses both absorption and adsorption refrigerators. It has advantages of being silent, having no compressor, lasting a long life cycle, and utilising waste heat or solar energy. In this work, the development of sorption refrigerators is outlined, and as a part of it, a theoretical diffusion absorption chiller using organic compounds is designed. The alternative working fluids used is R134a as the refrigerant, tetraethylene glycol dimethyl ether (TEG.DME) as the absorbent, and helium as the auxiliary gas. The corresponding modelling is carried out as a potential cooling system based on calculations. Furthermore, as a second part of this work, a laboratory prototype of a solid adsorption system being developed by the "Institute of Chemical Process Engineering (ICVT)" in Stuttgart University, is studied and compared. The study focuses on adsorption properties of methanol on activated carbon in adsorption process. Adsorption equilibrium data has been measured, and a good agreement between the measured equilibrium data and theoretical Dubinin-Astakhov model has been obtained. This prediction model can now be used to provide accurate data-sets, and consequently help to optimise the adsorption performance of the cooling unit. [Please note: this thesis file has been deferred until December 2016]